Increasing Family Economic Resilience During The Covid-19 Pandemic (Case Study of the Sidorejo Village Community, Tirto District, Pekalongan Regency) - Rizky Amalia; Muhammad Aris Safii (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2021)
Family economic resilience is closely related to the ability to manage the family economy which includes clothing, food, and housing so that it can be fulfilled even though it is minimalistic. The current shock of the Covid-19 pandemic has greatly impacted the distribution of household income and expenditure. Therefore, the purpose of this study is to find out what efforts can be made to increase family economic resilience during the pandemic. This research is a type of research that uses a literature study method and uses a qualitative approach. The results of this study indicate that there are four steps that can be taken as an effort to increase family economic resilience during the pandemic, namely by creating additional sources of income with an online shop business, optimizing family assets by optimizing the home yard, being able to manage family finances during the pandemic with financial planning and implementing a simple lifestyle by doing habits according to needs and abilities.